HUBUNGAN ANTARA EFIKASI DIRI DENGAN KECEMASAN MENGHADAPI PERTANDINGAN PADA ATLET DI SEKOLAH SEPAK BOLA APAC INTI - Leni DarmaWanti; Margaretta Erna Setianingrum (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2019)
This study aims to determine the relationship between self-efficacy with anxiety facing matches in athletes at the Apac Inti soccer school. Anxiety will arise when faced with something new such as facing a match. Athletes who master physical, technical, and good tactics, but if an athlete's mind is disturbed by excessive negative things, it can interfere with concentration and not optimal in the competition, causing athletes to feel anxious. The population in this study were 40 male students of Apac Inti aged 15-18 years. This research uses a quantitative correlational method with saturated sampling technique. Based on the research results obtained correlation coefficient (r) = -0.547; p <0.05 and it can be concluded that there is a significant negative relationship between self-efficacy with anxiety facing the match in athletes at Apac Inti soccer school.